Development and validation of an HPLC‐UV method for quantification of elvitegravir and two other new antiretrovirals, dolutegravir and rilpivirine, in the plasma of HIV‐positive patients. (31st May 2018) - Tempestilli, Massimo; Ammassari, Adriana; D'Avolio, Antonio; Cicalini, Stefania; Gallo, Anna Loredana; Fazio, Simone; Antinori, Andrea; Pucillo, Leopoldo P.
Abstract: Therapeutic drug monitoring may be crucial in selected clinical conditions for the management of HIV infection. In recent years, new antiretrovirals have been introduced and in particular elvitegravir (EVG) is now recommended for first‐line and simplification treatment as well as dolutegravir (DTG) and rilpivirine (RPV). The aim of this study was to develop and validate a high‐performance liquid chromatography–ultraviolet (HPLC‐UV) method for determining EVG and new antiretrovirals DTG and RPV in human plasma. Solid‐phase extraction was applied to a 600 μL plasma sample. Chromatographic separation of the three drugs and internal standard was achieved with a gradient of acetonitrile and phosphate buffer on a C18 reverse‐phase analytical column with a 20 min analytical run time. EVG and DTG were detected at 265 nm and RPV at 290 nm. Mean intra‐ and inter‐day precisions were < 10%; the mean accuracy was <15%. Extraction recovery ranged between 105 and 82% for the drugs analyzed. Calibration curves were optimized according to the expected ranges of drug concentrations in patients; the coefficient of determination was >0.997 for all drugs. This method allows for monitoring EVG, DTG and RPV in the plasma of HIV‐positive patients using HPLC‐UV.